The vasorelaxant mechanisms of methanol on isolated rat aortic rings: Involvement of ion channels and signal transduction pathways. (October 2017) - Bai, Y; Zhang, Q; Yang, Z; Meng, Z; Zhao, Q
It is reported that methanol is generally used as an industrial solvent, antifreeze, windshield washer fluid, cooking fuel and perfume. Methanol ingestion can lead to severe metabolic disturbances, blindness, or even death. So far, few studies about its negative effects on cardiovascular system have been reported. The purpose of this study was to determine the vasoactive effect of methanol and roles of ion channels and signal transduction pathways on isolated rat aorta. The results suggested that the mechanism of methanol-induced vasorelaxation at low concentrations (<500 mM) was mediated by ATP-sensitive K + (KATP ) and L-type Ca 2+ channels, but the mechanism at high concentrations (>600 mM) was related to KATP, voltage-dependent K +, big-conductance Ca 2+ -activated K +, L-type Ca 2+ channels as well as prostacyclin, protein kinase C, β-adrenoceptors pathways. In addition, methanol induced a dose-dependent inhibition of vasoconstrictions caused by calcium chloride, potassium chloride, or norepinephrine. Further work is needed to investigate the relative contribution of each channel and pathway in methanol-induced vasoactive effect.